A computational analysis on the implications of age-related changes in the expression of cellular signals on the role of IGF-1 in intervertebral disc homeostasis. Issue 2 (21st January 2015) - Asfour, Shihab; Travascio, Francesco; Elmasry, Shady; de Rivero Vaccari, Juan Pablo
Abstract Insulin-like growth factor-1 (IGF-1) is a well-known anabolic agent in intervertebral discs (IVD), promoting both proteoglycan (PG) biosynthesis and cell proliferation. Accordingly, it is believed that IGF-1 plays a central role in IVD homeostasis. The IGF-mediated anabolic activity in IVD occurs when the growth factor, free from binding proteins (IGFBP), binds to IGF cell surface receptors (IGF-1R). Previous studies reported that, with aging, cellular expression of IGFBP increases, while that of IGF-1R decreases. Both changes in cellular signals are thought to be among the factors that are responsible for the age-related decline in IGF-mediated PG biosynthesis, which ultimately leads to disc degeneration. In this study, a computational model describing the role of IGF-1 in the homeostasis of IVD was deployed in a parametric analysis to investigate the effects of age-related changes in expression of IGF-1R and IGFBP on the IGF-mediated upregulation of PG biosynthesis and cellular proliferation. It was found that changes in the expression of IGF-1R and IGFBP mostly affected the nucleus pulposus, while in the most external disc regions (annulus fibrosus and cartilage endplates) the IVD homeostatic balance was unaltered. It was shown that a decrease of IGF-1R expression caused reduction of both PG levels and cell density in the tissue. In contrast, increase in IGFBP expression increased both PG and cell concentration, suggesting that such change in cellular signaling may be a plausible defense mechanism from age-related IVD degeneration.